2008
DOI: 10.1038/onc.2008.346
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of cell polarity in EMT and cancer

Abstract: The epithelial-to-mesenchymal transition (EMT) is a crucial process in tumour progression providing tumour cells with the ability to escape from the primary tumour, to migrate to distant regions and to invade tissues. EMT requires a loss of cell-cell adhesion and apical-basal polarity, as well as the acquisition of a fibroblastoid motile phenotype. Several transcription factors have emerged in recent years that induce EMT, with important implications for tumour progression. However, their effects on cell polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
435
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(460 citation statements)
references
References 94 publications
(175 reference statements)
16
435
2
7
Order By: Relevance
“…Indeed, in addition to Snail, an increasing number of genes have been shown to orchestrate EMT. 32 We further showed that sorafenib negatively regulated the expression of other EMT-related transcription factors, including Twist, Zeb1, and Zeb2, but only had a subtle effect on the mRNA level of Slug (Fig. 5D).…”
Section: Resultsmentioning
confidence: 69%
“…Indeed, in addition to Snail, an increasing number of genes have been shown to orchestrate EMT. 32 We further showed that sorafenib negatively regulated the expression of other EMT-related transcription factors, including Twist, Zeb1, and Zeb2, but only had a subtle effect on the mRNA level of Slug (Fig. 5D).…”
Section: Resultsmentioning
confidence: 69%
“…During EMT, adherent epithelial cells lose basal-apical polarity and acquire a mesenchymal phenotype that includes enhanced migratory capacity, invasiveness, resistance to apoptosis and an increased production of extracellular matrix components [1]. Some of the hallmarks of EMT include loss of CD24 cell surface expression [2][3][4], downregulation of epithelial cytokeratins 8, 18 and 19 and E-cadherin, upregulation of vimentin, and mesenchymal transcriptional regulators such as Snai1 (Snail), Snai2 (Slug), Zeb1, Zeb2, Twist, FOXC1, and FOXC2 as reviewed in [5]. Mesenchymal cancer cells are more resistant to conventional chemotherapy and radiotherapy and correlate with tumor recurrence and a poor prognosis [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Snail is a conserved transcription factor that has been shown to play an important role in embryonic development and tumour progression 36 . Extensive analysis of such EMT inducers has clearly demonstrated a role in the direct regulation of cell polarity genes at the transcription level, contributing to the progression of cancer 37 . However, little information exists regarding the feedback regulation of these EMT inducers by cell polarity signalling.…”
Section: Discussionmentioning
confidence: 99%